Meaningful Productivity Strategy: The Key to Reducing Poverty In The 3T Region of The Mentawai Islands - Sabagalet, Yudas; Zulfa, Zulfa; Febrianto, Hary; Yatim, Yenita (Journal of Humanity Studies, 2025)
The Mentawai Islands, as one of Indonesia's Frontier, Outermost, and Disadvantaged (3T) regions, face the challenge of structural poverty that contradicts its rich natural resources. This study aims to formulate the concept of "Meaningful Productivity" as a poverty alleviation strategy that integrates local cultural values with modern economic efficiency. Using descriptive qualitative methods, this study found that conventional productivity, which focuses solely on physical quantities, often fails because it ignores the socio-cultural context of Arat Sabulungan. The results of the discussion indicate that downstreaming of local commodities (sago and coconut) and the development of community-based ecotourism are key pillars of meaningful productivity. This strategy has been proven to increase income while maintaining cultural identity, which is key to economic sustainability in the 3T region.